Archives of short-term fluid flow dynamics and possible influence of human activities at methane seeps: Evidence from high-resolution element geochemistry of chemosynthetic bivalve shells - Wang, Xudong; Fan, Danling; Kiel, Steffen; Gong, Shanggui; Liang, Qiangyong; Tao, Jun; Chen, Duofu; Feng, Dong (Frontiers in Marine Science, 2022)
The natural dynamics of fluid flow at methane seeps and increasingly human activities influence the biogeochemistry of the microenvironment and further determine the activity of the chemosynthetic communities within these ecosystems. However, ways to reconstruct short-term fluid flow dynamics and to decipher the influence of scientific exploration at seeps are limited. In this study, we present high-resolution trace elements/Ca ratios (Li/Ca, Mg/Ca, Ti/Ca, Mn/Ca, Co/Ca, Cu/Ca, Zn/Ca, Sr/Ca, Zr/Ca, Mo/Ca, Ba/Ca, Th/Ca and U/Ca ratios) from the shells of two species of chemosymbiotic bivalves (the thiotrophic vesicomyid clam Archivesica marissinica and the methanotrophic mussel Gigantidas haimaensis) from the Haima cold seeps of the South China Sea. We found that the complex distribution patterns of some trace elements (Mg/Ca, Sr/Ca, Mo/Ca and U/Ca ratios) in G. haimaensis are largely controlled by mineral composition or age. The observation of Co/Ca and Ba/Ca ratios in both species indicate strong physiological and environmental control on the incorporation of trace elements during the biomineralization process. Besides, the distribution patterns of other trace elements provide information that can be used to discuss open issues such as the loss of trace elements after death of the bivalves, and the possible influence of human activities such as sediment disturbance. Overall, this study emphasizes the potential for using high-resolution element geochemistry of seep bivalve shells to reveal the physiological and environmental factors that control the growth of bivalves, and to elucidate the potential history of fluid discharge at cold seeps.